Conference Chair - Ioannides, Marinos (My University, 2026)
A joint event for the exchange and sharing of know-how in the areas of Cultural Heritage (CH) and Information Technology (IT) focusing on e-documentation and 3D Computer Graphics:The 37th CIPA International Workshop dedicated on e-Documentation and Standardisation in Cultural Heritage (http://cipa.icomos.org)The 7th VAST International Symposium on Virtual Reality, Archaeology and Cultural Heritage.The 4th Eurographics Workshop on Graphics and Cultural Heritage (http://www.eg.org)The 1st Euro-Med Conference on IT in Cultural Heritage.EPOCH General Assembly (see conference programme)EPOCH SME meeting (see conference programme)CIPA Executive Commitee meetingThe 6th RecorDIM meeting (http://extranet.getty.edu/gci/recordim/)The event will provide an opportunity to exchange opinions, experiences and proposals on the best practice and tools to document, preserve and manage the Cultural Heritage, whether architectural, archaeological and/or natural. The main goal of the event is to illustrate the programs underway, whether organised by public bodies (e.g. UNESCO, European Union, National States, etc.) or by private foundations (e.g. Getty Foundation, World Heritage Foundation, etc.) in order to promote a common approach to the tasks of recording, documenting, protecting and managing the World Cultural HeritageTo reach this ambitious goal the topics covered will include experiences in the use of innovative recording technologies & methods and how to take best advantage of the results obtained to build up new instruments and improved methodologies for documenting and managing the Cultural HeritageIt is the first time that several organizations have decided to join together in order to create an optimal environment for the discussion, explanation of new technologies, exchange of modern ideas and in general to allow the transfer of knowledge between a maximum number of professionals and participants during one common time period.The 2006 joint event will focus on interdisciplinary and multi-disciplinary research concerning both innovative Cultural Heritage Informatics and use of technology for the representation, documentation, archiving and communication of CH knowledge. The scope includes every phase of CH information technology: initial data capture/digitization, information/data processing, visualization and documentation as well as dissemination of results to the scientific community and the general public, and the wider legal and ethical responsibilities of Cultural Heritage Informatics.Research subjects parallel the interests of CIPA, VAST, Eurographics and EPOCH EU Network , including culturally significant monuments, artefacts and sites as well as the activities of museums, libraries, archives, and organizations involved with their care.Those researchers who wish to participate in this event are invited to submit papers on original work addressing the following subjects or related themes:Data Acquisition Technologies focusing on Photogrammetry and Laserscanning,3D Data Capture and Processing in CHCAD and FEM based Digital Reconstructions and 3D ModellingReproduction Techniques and Rapid Prototyping in CHVisualisation Techniques (desktop, VR, AR)Multimedia, Data Management and Archiving2D and 3D GIS in CHNon-Photorealistic Rendering of CH DataComputer Animation for CH Applications and Virtual HeritageVirtual Museum Applications (e-Museums and e-Exhibitions)Novel Internet-based CH ApplicationsUsability, Effectiveness and Interface Design for CH ApplicationsInnovative Graphics Applications and TechniquesInteractive Environments and Applicationse-Libraries in Cultural Heritagee-Learning in CHTools for Education and Training in CHArchaeological Analysis and Interpretive DesignStandards and DocumentationProfessional and Ethical GuidelinesThe Economics of Cultural Informatics and TourismNatural and Man initiated deconstruction of Cultural Heritage and prevention techniques.